IRON CHELATING AND ANTIRADICAL ACTIVITY OF KAYU MANIK LEAVES (Trema orientalis) - Salprima Yudha S.; Eka Angasa; Sri Ningsih; Syalfinaf Manaf; Suli Anggria Murni; Fatan Umbara (Universitas Gadjah Mada, 2011)
A methanol soluble fraction extracted from Kayu Manik leaves (Trema orientalis) from Seluma, Bengkulu, exhibited an antiradical activity 69.73% (scavenging activity of the stable 1,1-diphenyl-2-picryl hydrazyl (DPPH) free radical) that was almost similar to that of 1 mM ascorbic acid. On the other hand, the iron chelating activity was 40.74%. We believe that it would be useful to take the results as an alternative for processing industries and can be observed as a good source of new agent for iron chelator.